AN ANALYSIS OF THE USE OF AUXILIARY VERB TA- BAKARI - Mariam Toliwongi (KOMPETENSI, 2021)
One sentence pattern in Japanese which means the same or synonym in Indonesian are ~ ta tokoro da and ~ ta bakari da which means "just now" but in usage there are differences according to the time span of the incident. The purpose of this study was to clearly determine the meaning, function of use and differences in sentence patterns of ~ ta tokoro da and ~ ta bakari da, besides that it also aims to determine the extent to which the students of semester 5th are able to use the two sentence patterns. This research is a descriptive method with data collection techniques using a written test to determine the ability of students to understand the use of ta-tokoro (た ー と こ ろ) and ta-bakari (た ー ば か り) in Japanese sentences, so that data must be processed and analyzed so that the data has meaning and meaning that can be understood as a result of the research that has been carried out then a conclusion is given.Based on the results of the study, it was found that the answers who had been the subjects in this study amounted to 15 people with an average value of 53.3% or in the range of ≥ 50%. Based on the test results, it can be seen that the ability of students of the Japanese Language Education Study Program, Faculty of Language and Arts, Universitas Negeri Manado, 5th semester, 2019/2020, in understanding sentences using ta-tokoro (た ー と こ ろ) and ta-bakari (た ー ば か り) have pretty good.